Comparison of indirect and descriptive methods of functional behaviour assessment in adults with intellectual disability - Simnjanovski, Maja; Žgur, Erna (Specijalna edukacija i rehabilitacija, 2025)
Introduction. Adults with intellectual disability exhibit challenging behavior more frequently than the population with typical development. Functional behavior assessment is an effective and scientifically-based way of reducing individual challenging behavior. Two types of methods are used in the functional behavior assessment process: indirect and descriptive. Aim. The purpose of this research was to examine the consistency between the results obtained using both methods. Methods. A multiple case study included three adults with moderate intellectual disability. Two people were 18 years old and one person was 19 years old. All three people showed different forms of challenging behavior. Data was collected using indirect and descriptive methods. We compared the findings of the function of the challenging behavior using both methods. Although three participants were included in the study, we collected data related to the function of behavior for four different forms of challenging behavior. Results. In the case of the first participant, the same function of problematic behavior, ʼdisobeying the rulesʼ, was determined by using both methods of functional behavior assessment, which was ʼgetting attentionʼ. In the case of the second participant, only one form of problematic behavior, ʼtalking to oneselfʼ, obtained the same function of problematic behavior, which was ʼgetting attentionʼ, while another form of problematic behavior, ʼrepeating the same phrasesʼ, obtained a different function. In the case of the third participant, different results were obtained for problematic behavior ʼnon-cooperationʼ. Conclusion. The research showed that data related to the function of challenging behavior were consistent only in two cases (50%). Considering the obtained results, the results about the function of problematic behavior obtained using only one method of functional assessment of behavior should be interpreted with caution.